John Milton : Epistolarum Familiarium Liber Unus and Uncollected Letters - Milton, John, 1608-1674 (Supplementa humanistica Lovaniensia ;, 2019)
First full-scale edition of John Milton's Latin and uncollected vernacular letters. John Milton holds an impressive place within the rich tradition of neo-Latin epistolography. His Epistolae Familiares and uncollected letters paint an invigorating portrait of the artist as a young man, offering insight into his reading programme, his views on education, friendship, poetry, his relations with continental literati, his blindness, and his role as Latin Secretary. This edition presents a modernised Latin text and a facing English translation, complemented by a detailed introduction and a comprehensive commentary. Situating Milton's letters in relation to the classical, pedagogical, neo-Latin, and vernacular contexts at the heart of their composition, it presents fresh evidence in regard to Milton's relationships with the Italian philologist Benedetto Buonmattei, the Greek humanist Leonard Philaras, the radical pastor Jean de Labadie, and the German diplomat Peter Heimbach. It also announces several new discoveries, most notably a manuscript of Henry Oldenburg's transcription of Ep. Fam. 25.